A recent trend of drug-nanoparticles in suspension for the application in drug delivery. (November 2016) - Suri, Gurpreet S; Kaur, Amritvir; Sen, Tapas
Persistent development in nanomedicine has enabled successful nanosizing of most drug samples which, in turn, imparts remarkable properties to the drugs such as enhanced solubility and bioavailability for the applications in drug delivery. In this context, several review articles are available in scientific domain covering inorganic nanoparticles such as Au, Ag, SPIONs, Qdots, carbon nanotubes and graphene; however, this review covers the development of drug nanoparticles together with their possibilities and limitation from fabrication (bottom up vs top down) to application in drug delivery during the last 5 years. In addition, some distinguished studies and novel drug particles are presented in order to contribute significantly toward the understanding of drug nanocrystals and its use in drug delivery.